Examining the transfer of knowledge and training to smallholders in India: direct and spillover effects of agricultural advisory services in an emerging economy - Varshney, Deepak; Joshi, Pramod K.; Kumar, Anjani; Mishra, Ashok K.; Dubey, S. K. (Elsevier, 2022)
We evaluate a large-scale model of agricultural advisory services, known as Krishi Vigyan Kendra (KVK) or Farm Science Centers, introduced by the Government of India to facilitate smallholder adoption of new agricultural technologies. The study first evaluates the impact of frontline demonstrations and capacity-building programs conducted by KVKs and aimed at promoting a new wheat variety (HD2967); it then examines gains in the speed of diffusion at the district level. The study’s second objective is to estimate the spillover effects of KVKs through social networks. The study identifies network beneficiaries based on a ‘‘networks within sample” approach. The study uses a matched difference-indifferences approach and sample of 1496 wheat farmers in Uttar Pradesh, India. The finding shows that frontline demonstrations and capacity-building programs positively impact the adoption of HD-2967. The magnitude of the impacts is larger for KVK beneficiaries, but substantial gains also arise for network beneficiaries. The study underscores the importance of frequently conducting interventions to influence adoption on aggregate at the district level. From a policy perspective, the study offers new insights for strengthening outreach and extension services designed to facilitate the transfer of agricultural knowledge and information, emphasizing frontline demonstrations, capacity-building programs, and spillovers in extending the scope of KVKs.